Safety factors and risk in fatigue substantiation of helicopter components - Toulas, N. (Cranfield University, 2005)
Helicopter dynamic components are substantiated against fatigue using the safe life methodology. The advance of usage monitoring systems suggest the extension of the safe life according to measured usage, leading to maintenance credits. The question is whether the extended life is associated with a different probability of failure due to elevation of safety factors embedded within the safe life methodology. The fatigue substantiation process was studied and its conservatisms were identified. Both S-N curve behaviour and service loading have been investigated. Three components were studied. One was a location on the lift frame, the others were a main rotor blade linkage and a rotor pitch change link. The variation in manoeuvre loads and usage during normal operation of a UK military helicopter was statistically estimated. Service loads were measured using strain gauged components and a data recording system. Usage was monitored by manual identification and recording of manoeuvres throughout the helicopter flight. It was found that usage variability is very great, with coefficients of variation in excess o f 100% for the majority of manoeuvres. It was found that usage measured in service was significantly more benign for all types of mission, than that assumed in design. Mechanical test results showed significant errors in damage accumulation and mean stress models for life prediction. Monte Carlo simulations demonstrate that calculated probability of failure is dominated by material and modelling errors; usage and manoeuvre load variability playing a minor role.